Spirituality in alternative correctional method on hard core drug addict: case study of “Anak Bina Inabah” - Maamor, Selamah; Abdul Ghani, Abdullah; Aziz, Ahmad Bashir; Ahmad Razimi, Mohd Shahril; Abdul Wahab, Norazlina; Elias, Nor Hanim; Nik Abdullah, Nik Safiah (Universiti Teknologi Malaysia, 2016)
This article is part of a larger study on the role of spirituality in correcting/rectifying the hard core drug addict.The study seeks to reveal the meaning of the experience through the stories of three Muslim who used to involve with drug addiction, to better understand the deep meanings that inform their experiences with spirituality and transformation as they cope with the challenges of drug addict.Data were gathered using in depth interview. Qualitative methods were used in identifying two themes which are closer to Allah will make them far from drug and fulfill soul to rectify physical and spiritual.The themes were discussed in the context of two broad areas: (1) what are the new meanings these man discovered in their experiences in drug addiction; and (2) how did the new meanings (change their lives).The study suggests that former drug addict experiences with drug addict and their learning processes must be understood within the appropriate cultural context. The common emphasis of spirituality on relationship with God, self and others, may significantly influence how people learn to live without drug.